Socio-economic impact of the solidarity economy sector in Boyacá, Colombia. 2000 - 2009 (2012)
The sector of the solidarity economy plays an important role at the economic and social level. Although it is theoretically recognized, there is a limited academic production of the solidarity sector in Boyacá. That is why, from the supportive business model, the socio- economic sector is analyzed in the solidarity sector in Boyacá 2000-2009, under the descriptive method. The results show that this sector advances achieving a higher position in the solidarity economy, at the national and sectional level. The figures reveal the socio- economic dynamic of the sector, its evolution and growth. The findings suggest further studies on the solidarity economy sector in Boyacá.